Pendampingan Manajemen OJS Zona Kebidanan Sebagai Wadah Publikasi Penelitian Di Universitas Batam - Frangky Silitonga; M Muthma'innah; Agung Prapsetyo; Arum Dwi Anjani (SIGMA : Jurnal Sinergi Mengabdi, 2024)
The publication of this activity is a service as a result of assistance in preparing the Zona Kebidanan for accreditation in a national journal. The Zona Kebidanan publishes research results three times a year. This Zona Kebidanan assistance and management activity is a collaborative service between Batam Tourism Polytechnic and Batam University. The target of achieving this assistance is to complete the publication of journal house ethics and integrate it into the Zona Kebidanan, the functions and results of Community Service (PKM) activities carried out by the Batam University academic community. This PKM was implemented boldly and offline from the Batam Tourism Polytechnic and Batam University. The PKM implementation method is carried out face-to-face with the aim of managing the OJS Zona Kebidanan, while the bold method aims to complete administration at BRIN and internally. The face-to-face methods used are lectures, role plays and demonstrations as well as direct training which has been scheduled regularly and in a structured manner.